Heterosis in Bitter Gourd (Momordica charantia L.) - Murlee Yadav (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2009)
The present investigation was conducted to determine heterosis in 6 lines and 4 tester crosses of bitter gourd, where the six lines used were MC-84 (L1), S-17 (L2), JMC-21 (L3), NDBT-15(L4), VRBT-94 (L5) and Gy-1 (L6) and the four testers were VRBT-6-9 (T1), JMC-22 (T2), VRBT-89 (T3) and MC-56 (T4). Most of the crosses failed to manifest significant heterosis for many of the horticultural traits but traits, like vine length and fruit length showed positive significant heterosis, while, days to first appearance of female flower manifested negative significant heterosis in several crosses. Two crosses, namely, MC-84 x VRBT-6-9 and MC-84 x JMC-22 were identified to have potential in terms of yield, whereas two more crosses viz., S-17 x VRBT-6-9 and S-17 x JMC-22 were found superior in terms of powdery mildew resistance.